High permeability explains the vulnerability of the carbon store in drained tropical peatlands. Issue 3 (9th February 2017) - Baird, Andy J.; Low, Robert; Young, Dylan; Swindles, Graeme T.; Lopez, Omar R.; Page, Susan
Abstract: Tropical peatlands are an important global carbon (C) store but are threatened by drainage for palm oil and wood pulp production. The store's stability depends on the dynamics of the peatland water table, which in turn depend on peat permeability. We found that an example of the most abundant type of tropical peatland—ombrotrophic domes—has an unexpectedly high permeability similar to that of gravel. Using computer simulations of a natural peat dome (NPD) and a ditch‐drained peat dome (DPD) we explored how such high permeability affects water tables and peat decay. High permeability has little effect on NPD water tables because of low hydraulic gradients from the center to the margin of the peatland. In contrast, DPD water tables are consistently deep, leaving the upper meter of peat exposed to rapid decay. Our results reveal why ditch drainage precipitates a rapid destabilization of the tropical peatland C store. Key Points: Permeability of the most common type of tropical peatland is higher than expected and like that of unconsolidated gravel High permeability does not cause rapid drainage of undisturbed tropical peatlands High permeability leads to deep water tables in ditched tropical peatlands, and associated high rates of peat oxidation